2005
DOI: 10.1007/s11104-004-1658-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a ‘Free Ion Activity Model’ applied to metal uptake by Lolium perenne L. grown in contaminated soils.

Abstract: We investigated several formulations of the 'free ion activity model' (FIAM) as a means of describing plant uptake of soil Cd and Zn from contaminated soils. Lolium perenne was grown on a range of urban and metal-spiked agricultural soils selected to provide a wide range of Cd and Zn concentrations, pH values and other physicochemical properties. Plants were grown under controlled conditions and above-ground biomass was harvested at regular intervals. Concentrations of Cd and Zn in the grass were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 23 publications
2
36
2
Order By: Relevance
“…The distribution of a metal between solid and liquid phases is then modelled with an equilibrium partitioning model, and the plant response (uptake or toxicity) is modelled from the solution composition using a FIAM or BLM approach. [42][43][44][45][46] These models give reasonable predictions of the uptake, but this does not prove that the 'equilibrium' assumptions behind the model are valid. For example, Hough et al [46] showed that the prediction using a FIAM approach was not superior to that of a simple empirical regression model.As pointed out by the authors, the derived 'reaction constants' could truly represent an equilibrium condition, in which case they describe the affinity of metal and proton ions for the root sites, but they could also be fitting parameters in a transport-limited uptake process.…”
Section: Free Ion Activity Model (Fiam) and Biotic Ligand Model (Blm)mentioning
confidence: 93%
“…The distribution of a metal between solid and liquid phases is then modelled with an equilibrium partitioning model, and the plant response (uptake or toxicity) is modelled from the solution composition using a FIAM or BLM approach. [42][43][44][45][46] These models give reasonable predictions of the uptake, but this does not prove that the 'equilibrium' assumptions behind the model are valid. For example, Hough et al [46] showed that the prediction using a FIAM approach was not superior to that of a simple empirical regression model.As pointed out by the authors, the derived 'reaction constants' could truly represent an equilibrium condition, in which case they describe the affinity of metal and proton ions for the root sites, but they could also be fitting parameters in a transport-limited uptake process.…”
Section: Free Ion Activity Model (Fiam) and Biotic Ligand Model (Blm)mentioning
confidence: 93%
“…These regression models have helped develop understanding of the robustness of the relationships between solution metal and soil characteristics 12 . More recently, the free metal ion concentration or activity has been identified as the solution species that provides robust 20 predictions of plant and microbial uptake of metals based on the Free Ion Activity Model (FIAM) or Biotic Ligand models 16,17 . Soil Critical Limits for Zn, Cd and Pb have been developed based on free ion concentrations in solution 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…The total pool is usually larger than the reactive pool, and the difference between both is considered to be nonreactive or inert, at least on a time scale of years to decades. The directly available pool can be related to uptake of metals by soil organisms and plants (Saxe et al 2001;Lofts et al 2004, Hough et al 2005Peijnenburg et al 2007;Koopmans et al 2008a). Both the total dissolved concentration and the free metal ion activity in solution have been used as a measure of the directly available pool (Saxe et al 2001;Lofts et al 2004, Hough et al 2005Peijnenburg et al 2007).…”
mentioning
confidence: 99%
“…The directly available pool can be related to uptake of metals by soil organisms and plants (Saxe et al 2001;Lofts et al 2004, Hough et al 2005Peijnenburg et al 2007;Koopmans et al 2008a). Both the total dissolved concentration and the free metal ion activity in solution have been used as a measure of the directly available pool (Saxe et al 2001;Lofts et al 2004, Hough et al 2005Peijnenburg et al 2007). Since it is difficult to obtain real soil solution samples, soil extracts such as a 1:10 w/v soil-solution extract using 0.01 M CaCl 2 (Houba et al 2000) are believed to represent the directly available pool in soil (Degryse et al 2003).…”
mentioning
confidence: 99%